Relation nitrate/ammonium/urea and potassium concentration in hydroponic tomato production - Parra Terraza, Saúl; Mendoza Palomares, Guadalupe; Villarreal Romero, Manuel (Revista Mexicana de Ciencias Agrícolas, 2018)
Tomato plants (Solanum lycopersicum L. cv. IB-9) were grown in a hydroponic system in order to evaluate the effect of the ratio nitrate, ammonium, urea (100/0/0, 85/15/0, 85 / 0/15 and 85/7.5/7.5) and the concentration of potassium (7 and 9 mol m-3) in fruit yield and mineral composition of plants. The fruit yield was unaffected by the treatments, so that it can substitute 15% of the total nitrate nitrogen to the nutrient solution with an equal percentage of nitrogen or urea, or a mixture of ammonia and urea, each at 7.5 %. The phosphorus content in leaves was significantly increased by the interaction of 85/15/0 and 9 mol of potassium m-3, while the calcium concentration in leaves 100/0/0 statistically decreased and 9 mol m-3 potassium.
Keywords: Solanum lycopersicum L.; nutrient content; hydroponic; nutrient solutions